Mastofauna associated with culverts along a road within the Yasuní National Park, Ecuador - Auz-Cerón, David Alejandro; Mejía-Valenzuela, Edison Gabriel; Macas-Pogo, Patricio; Tonato, Luis (Therya Notes, 2023)
Road construction is one of the main boosters of biodiversity loss. Fortunately, culverts can function as passes for certain wildlife species. This study recorded the mammal species that may use these structures to move from one side of a road to the other. The mammals visiting 11 culverts on a road within the Yasuní National Park were recorded over a month using camera traps. The capture rate (TC) and the visitation rate (TV) were calculated to quantify the most visited site and the most frequent visitor species. A sampling effort of 365 camera-trap days yielded 7,110 records with 264 independent events corresponding to 10 mammal species. The highest visitation rates corresponded to Cuniculus paca (52.05) and Mazama americana (9.86); the other species had a visit rate lower than 3. Cuniculus paca was recorded in 10 culverts. Cuniculus paca was the only species recorded inside a culvert; however, we cannot conclude that it crossed from one side to the other. The rest of the species approached the culverts, but there was no evidence of their entry. The use of culverts likely depends on the construction characteristics and the required conditions. However, implementing culverts can mitigate adverse impacts to the fauna, so future research is necessary.